The p.T191M mutation of the CBS gene is highly prevalent among homocystinuric patients from Spain, Portugal and South America (2006)
Classical homocystinuria is due to cystathionine b-synthase (CBS) deficiency. More than 130 mutations, which differ in prevalence and severity, have been described at the CBS gene. Mutation p.I278T is very prevalent, has been found in all European countries where it has been looked for with the exception of the Iberian peninsula, and is known to respond to vitamin B6. On the other hand, mutation p.T191M is prevalent in Spain and Portugal and does not respond to B6. We analysed 30 pedigrees from Spain, Portugal, Colombia and Argentina, segregating for homocystinuria. The p.T191M mutation was detected in patients from all four countries and was particularly prevalent in Colombia. The number of p.T191M alleles described in this study, together with those previously published, is 71. The prevalence of p.T191M among CBS mutant alleles in the different countries was: 0.75 in Colombia, 0.52 in Spain, 0.33 in Portugal, 0.25 in Venezuela, 0.20 in Argentina and 0.14 in Brazil. Haplotype analyses suggested a double origin for this mutation. No genotype–phenotype correlation other than the B6-nonresponsiveness could be established for the p.T191M mutation. Additionally, three new mutations, p.M173V, p.I429del and c.69_70+8del10, were found. The p.M173V was associated with a mild, B6-responsive, phenotype